Neo-Nazism and discrimination against foreigners: A direct test of taste discrimination - Nils Braakmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
I test some predictions of Gary Becker's theory of taste discrimination regarding discrimination of foreigners by employers, co-workers and customers. I combine a 2% sample of the German working population and a 50% sample of German plants with low-level regional data, including the vote shares of three right-wing parties as a proxy for regional racism. The results show that (a) foreigner-native wage differentials rise with the share of right-wing voters, (b) the exact magnitude of the effects varies between skill groups and by gender, the largest effects being found for high-skilled men and women, (c) average employment shares of natives vary very little with the share of right-wing voters, (d) segregated firms become more common in manufacturing and construction when support for right-wing parties rises, while no effects are found for services and gastronomy and (e) the negative wage effects are strongest for foreigners working in services, while no effects are found in manufacturing and gastronomy. These results broadly confirm the predictions from taste discrimination.
Keywords: J23; J31; J71; 330; taste discrimination; segregated firms; wage differentials